2001
DOI: 10.1590/s0100-69912001000300011
|View full text |Cite
|
Sign up to set email alerts
|

Linfonodo sentinela: um novo conceito no tratamento cirúrgico do câncer de mama

Abstract: O linfonodo sentinela é o primeiro linfonodo que recebe a drenagem linfática proveniente do câncer de mama. A sua detecção tem a finalidade de predizer o estado da axila e evitar o esvaziamento axilar nos pacientes sem comprometimento metastático. Os autores realizaram uma ampla revisão da literatura, envolvendo os aspectos cirúrgicos, de Medicina Nuclear e de Anatomia Patológica do linfonodo sentinela. Muitos estudos demonstraram a eficácia do linfonodo sentinela em predizer o comprometimento axilar. Entretan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
10

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 35 publications
0
3
0
10
Order By: Relevance
“…There are approximately 1000 new cases every year and it accounts for a significant number of deaths among adult women, thus is a severe public health problem [1].…”
Section: Introductionmentioning
confidence: 99%
“…There are approximately 1000 new cases every year and it accounts for a significant number of deaths among adult women, thus is a severe public health problem [1].…”
Section: Introductionmentioning
confidence: 99%
“…However, in 33.3% (3/9), no SLN was ever seen and these patients, then, underwent AL. In these three cases, the exam with HE ascertained that 71.9% (46/64) of the dissected lymph nodes were involved with tumor (Table 1) Urban et al (2001) and Xavier et al (2005) found that advanced age can contribute to radiopharmaceutical failure in identifying the SLN, possibly due to liposubstitution of the lymphoid tissue. Birdwell et al, (2001) suggested that lower rates of SLN identification related to age were due to decreased breast tissue turgor in older women, resulting in lower hydrostatic pressure in the lymphatic channels and lower impulsion power of the radiocolloid, besides the decreased phagocytic function of the lymph node itself, which in older women shows reduction of the sinusoidal spaces due to liposubstitution.…”
Section: Resultsmentioning
confidence: 95%
“…Previously, many patients have undergone ALND, even in the absence of metastatic disease. Thus, the concept of sentinel lymph node biopsy (SLNB) [11] for breast cancer [12, 13] emerged and is characterized as a high-accuracy method for determining the axillary state, with a low axillary recurrence even with a considerable false-negative rate of up to 10% [14-19]. Thus, SLNB was established as the standard method for determining axillary status in breast cancer in clinically N0 patients.…”
Section: Introductionmentioning
confidence: 99%